The Change in Hemoglobin Levels Before and After Cesarean Section and its Association with Age and Parity in Pregnant Women at Yarsi Hospital from January to October 2025 and Its Review According to Islam - Tawfiqah Tsurayya; Syukrini Bahri; Afrizal Tw; Endah Purnamasari (Green Publisher Indonesia, 2026)
This research aimed to analyze changes in hemoglobin levels before and after cesarean section and their association with maternal age and parity in pregnant women at YARSI Hospital from January to October 2025, as well as to review cesarean section from an Islamic perspective. This study employed a descriptive analytic design with a retrospective approach using secondary data obtained from medical records. A total of 292 pregnant women who underwent cesarean section and met the inclusion criteria were selected through consecutive sampling. Data analysis included univariate and bivariate analyses, using a paired t-test to assess differences in hemoglobin levels before and after cesarean section and a chi-square test to examine the relationship between age, parity, and changes in hemoglobin levels. The results showed that the mean hemoglobin level before cesarean section was 11.67 g/dL and after cesarean section was 11.78 g/dL, with no statistically significant difference between the two measurements. Furthermore, there was no significant association between maternal age or parity and changes in hemoglobin levels. From an Islamic perspective, cesarean section is permissible as it aligns with the principle of Hifz al-Nafs (protection of life) within Maqasid Shari‘ah, provided it is performed based on medical indications and aims to prevent harm to the mother and fetus. In conclusion, cesarean section at YARSI Hospital did not result in significant changes in hemoglobin levels and was not influenced by maternal age or parity, while remaining consistent with Islamic medical ethics.